Restoring marine ecosystems: Spatial reef configuration triggers taxon‐specific responses among early colonizers. Issue 12 (28th September 2021) - Wilms, Tim J. G.; Norðfoss, Pauli H.; Baktoft, Henrik; Støttrup, Josianne G.; Kruse, Bo M.; Svendsen, Jon C.
Abstract: The longstanding debate in conservation biology on the importance of single large or several small (SLOSS) habitats for preserving biodiversity remains highly relevant, given the ongoing degradation and loss of natural habitats world‐wide. Restoration efforts are often constrained by limited resources, and insights from SLOSS studies therefore have important implications if restoration efforts can be optimized by manipulating the spatial configuration of restored habitats. Yet, the relevance of SLOSS for habitat restoration remains largely unexplored. Here, we report the effects of spatial reef configuration on early colonization of marine organisms after restoring boulder reef habitats. Reefs were restored in single large (SL) and several small (SS) designs in the western Baltic Sea, where century‐long boulder extraction has severely degraded large reef areas and likely exacerbated regional declines in commercially important gadoids ( Gadidae spp.). We sampled the field sites using remote underwater video systems in a before‐after control‐impact (BACI) design and obtained probabilistic inferences on restoration and SLOSS effects from Bayesian hierarchical models. Probabilities of a positive restoration effect were high (>95%) for gadoids, labrids and demersal gobies, moderate (60%–75%) for species richness and sand gobies, and low (<5%) for flatfish abundance. Notably, gadoid abundance increased 60‐fold and 129‐fold on average at SL and SS respectively. The species composition at restored reefs deviated from control sites, mainly driven by large‐bodied piscivores. Spatial reef configuration had the strongest effect on small‐bodied mesopredators, including gobies, which were more abundant at SS and driving distinct species assemblages between the reef designs. In addition to providing suitable conditions for reef species, results suggest that SS can also benefit soft‐bottom taxa, possibly through a dispersed predator‐mediated effect relative to SL. Synthesis and applications . This study demonstrates that boulder reef restoration can strongly promote the abundance of exploited gadoids (e.g. Atlantic cod) and is therefore a promising management tool to support top‐down controls by predatory fishes in degraded marine systems. The higher abundance of mesopredators at reefs with a 'several small' configuration suggests that the SLOSS dilemma could have long‐term implications for trophic structure and resilience of restored habitats, and should therefore become an important facet within restoration strategies. Abstract : This study demonstrates that boulder reef restoration can strongly promote the abundance of exploited gadoids (e.g. Atlantic cod) and is therefore a promising management tool to support top‐down controls by predatory fishes in degraded marine systems. The higher abundance of mesopredators at reefs with a 'several small' configuration suggests that the 'single large or several small' (SLOSS) dilemma could have long‐term implications for trophic structure and resilience of restored habitats, and should therefore become an important facet within restoration strategies. Resumé: Iforbindelse med beskyttelse af dyrs og planters levesteder har man længediskuteret, om det er bedst at beskytte ét stort område eller mange små områder(ESEMS‐diskussionen). Spørgsmålet er stadigvæk relevant, fordi levestederfortsat går tabt mange steder i verden. Levestederne kan restaureres, menprojekterne har ofte begrænsede midler til rådighed. Viden fraESEMS‐undersøgelser er derfor vigtig, fordi resultaterne frarestaureringsprojekter formodentligt bliver bedre, hvis den rummelige udbredelseaf de restaurerede levesteder optimeres i forhold til ESEMS. Men viden fraESEMS‐undersøgelser anvendes desværre fortsat sjældent irestaureringsprojekter. Inærværende studie rapporterer vi effekterne af forskellige rummeligeudbredelser af restaurerede stenrev i forhold til kolonisering af marineorganismer. Stenrevene blev enten restaureret som enkelte store (ES) stenreveller som mange små (MS) stenrev. Projektet blev udført ved Sønderborg Bugt, hvor opfiskning af sten har fundet sted igennem årtier, hvilket har reduceretantallet af naturligt forekommende stenrev. De manglende stenrev betyder bl.a., at torskefisk (Gadidae spp.) har færre levesteder. Vi brugte undervandskameraertil at undersøge kontrolområder og kommende revområder både før og efterudlægning af stenrev. Data fra videooptagelserne blev anvendt til at estimereeffekterne af de udlagte stenrev. Analyserneviste, at sandsynligheden for en positiv restaureringseffekt var høj (> 95%)for torskefisk, læbefisk og bundlevende kutlinger, moderat (60%–75%) forartsrigdommen og sandkutlinger, og lav (<5%) for fladfisk. Gennemsnitligtsteg forekomsten af torskefisk 60 gange ved ES stenrev og 129 gange ved MSstenrev. Detvar især smådyr som kutlinger, der var påvirkede af forskellighederne istenrevenes rummelige udbredelse. Der var højere forekomst af smådyrene ved MSstenrev, hvor der ligeledes var en særlig artssammensætning af smådyrene.Resultaterne viser, at restaurerede stenrev giver levesteder til en rækkerev‐arter, der formodentligt drager nytte af nærliggende blødbundsområder iforbindelse med MS stenrevene. Syntese og anvendelse . Voresundersøgelse viser, at restaurering af stenrev i høj grad kan forøgeforekomsterne af torskefisk. Restaurering af stenrev er derfor et lovendeværktøj til at genskabe tidligere forekomster af rovfisk som torsk, der kanpåvirke havets fødekæder og økosystemer positivt ved at æde en række mindreorganismer. De højere forekomster af smådyr som kutlinger ved MS stenreveneindikerer, at ESEMS overvejelser kan have langsigtede konsekvenser forfødekæder og økosystemers modstandsdygtighed ved restaurerede levesteder. Derfor bør ESEMS overvejelser integreres ifremtidige restaureringsstrategier.